MENGGUNAKAN MULTIMEDIA INTERAKTIF DALAM PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS V SDN 241 PALEMBANG - Elvira Anjelia; Effendi Effendi; David Saputra (JOURNAL SAINS STUDENT RESEARCH, 2024)
The average time of abad 21 terutama in Indonesia is also significant, part of the world education. The educational curriculum of diidonesia at the same time as the curriculum of the year. Curriculum Merdeka focuses on intracurricular teaching, which mentioned by three teachers as a way to introduce teaching with careful consideration and practical consideration. Salah satunya penguin technology is the focus of the entire organization in the implementation of the National Curriculum. With effective technology, customers can enjoy more personal, mechanical, and personal information about their customers. Penelitian ini vertujuan for meningkat achieving peserta didik class VB for students of mathematics. Metode penelitian which is developed as a penalty shop class (PTK) which is taught in 2 cycles. Design penelitian texture covered with permanent, light, transparent, and reflective. Data collected through a wide range of technical documentation, analysis, observation, and testing. Berdasarkan hasil penelitian, hasil belajar peserta didik mengalami peningkatan. Then they increased by 44%. After each cycle I presentation increased the yield to 74%. Meskipun mengalami peningkatan pada perbaikan cycle I mass pearl perbaikan lagi dikarenakan belum mencapai ketuntasan yang diinginkan. Eventually perbaikan cycle II, none of the patients achieved a significant increase above 93%. From the achievement that can be achieved first, it can be simple to mention the media pembelajaran basic technology to increase the achievement of the peserta didik to the eyes of mathematics students.